ANALISIS PENGARUH BRAND IMAGE, VANITY SEEKING DAN MATERIALISM TERHADAP MINAT BELI ULANG JASA KECANTIKAN (STUDI KASUS PADA KIMLY AESTHETIC CLINIC DI PANGKALPINANG) - Jessica; Medinal; Ruben Manullang, Rizal (STIE IBEK Pangkalpinang, 2021)
This research was entitled: “Analisis Pengaruh Brand Image, Vanity Seeking Dan Materialisme Terhadap Minat Beli Ulang Jasa Klinik Kecantikan (Studi Kasus Pada Kimly Aesthetic Clinic di Pangkalpinang)”. The background of this research is based on existing phenomena showing that the competition among face and beauty clinic during the pandemic. The purpose of this study was to determine and examine the effect of brand image, vanity seeking, materialism on repurchase intention, both simultaneously and partially. The method of research is a descriptive quantitative study with a sample size of 51 respondents. This study has three independent variables; brand image, vanity seeking, and materialism. The dependent variable was labeled as a repurchase intention. Testing instruments are using validity and reliability tests. The data analysis method used in this study is Multiple Linear Regression Analysis using the F-test along with Simple Linear Regression with T-test. Also the researcher use an analysis of the Coefficient of Determination (R2) in order to provide empirically the ability to explaining the dependent by three independence variables simultaneously. The results of the research on the independent variable brand image (X1) obtained t-count 1,485 < t-table 1.677, vanity seeking variable (X2) with t-count 2,672 > t-table 1.677 and materialism variable (X3) with t-count 3,904 > t-table 1.677. Therefore, a brand image does not have a partial effect towards a repurchase intention,, a vanity seeking has a partial effect towards repurchased intention. Also, the study stated if digital materialsim also has a partial a partial effect towards repurchase order. The results of the F-test show that F-count 52.758 > F-table 2.80. This means that the independent variables (brand image, vanity seeking and materialism) simultaneously have an affect towards the dependent variable (repurchase intention). The test results of the Coefficient of Determination (R2) show Adjusted R-Square 0.756 or in other word, that repurchase intention variable can be explained by variables brand image, vanity seeking and materialism by 75.6%. While the remaining 0.244 or 24.4% can be explained by other variables outside the research variables.